Childhood trauma and treatment outcomes during mood‐stabilising treatment with lithium or quetiapine among outpatients with bipolar disorder. (11th March 2022) - Wrobel, Anna L.; Köhler‐Forsberg, Ole; Sylvia, Louisa G.; Russell, Samantha E.; Dean, Olivia M.; Cotton, Sue M.; Thase, Michael; Calabrese, Joseph R.; Deckersbach, Thilo; Tohen, Mauricio; Bowden, Charles L.; McInnis, Melvin G.; et al.
Abstract: Background: Childhood trauma affects the course of mood disorders. Researchers are now considering childhood trauma as an influential factor in the treatment of mood disorders. However, the role of childhood trauma in the treatment of bipolar disorder remains understudied. Methods: The effect of childhood trauma on treatment outcomes was evaluated among participants randomised to treatment with lithium or quetiapine in the Clinical and Health Outcomes Initiatives in Comparative Effectiveness for Bipolar Disorder (Bipolar CHOICE) study by clinician assessment. Mixed effects linear regression models were used to analyse rates of improvement in symptom severity (assessed with the Bipolar Inventory of Symptoms Scale and the Clinical Global Impression Scale for Bipolar Disorder) and functional impairment (assessed with the Longitudinal Interval Follow‐up Evaluation‐Range of Impaired Functioning Tool). Results: A history of any childhood trauma was reported by 52.7% of the sample ( N  = 476). Although participants with a history of any childhood trauma presented with greater symptom severity and functional impairment at most study visits, participants with and without a history of any childhood trauma showed similar rates of improvement in symptom severity and functional impairment over the 24 weeks of treatment. Conclusion: This is the first study to explore the association between childhood trauma and treatment outcomes during treatment with lithium or quetiapine in the context of a randomised trial. In Bipolar CHOICE, a history of childhood trauma did not inhibit improvement in symptom severity or functional impairment. Nevertheless, these findings need replication across different settings.